Metal-based nanostructured materials for advanced lithium-sulfur batteries - Balach, Juan Manuel (2018)
Since the resurgence of interest in lithium-sulfur (Li-S) batteries at the end of the 2000s, research in the field has grown rapidly. Li-S batteries hold great promise as the upcoming post-lithium-ion batteries owing to their notably high theoretical specific energy density of 2600 W h kg−1, nearly five-fold larger than that of current lithium-ion batteries. However, one of their major technical problems is found in the shuttling of soluble polysulfides between the electrodes, resulting in rapid capacity fading and poor cycling stability. This review spotlights the foremost findings and the recent progress in enhancing the electrochemical performance of Li-S batteries by using nanoscaled metal compounds and metals. Based on an overview of reported functional metal-based materials and their specific employment in certain parts of Li-S batteries, the underlying mechanisms of enhanced adsorption and improved reaction kinetics are critically discussed involving both experimental and computational research findings. Thus, material design principles and possible interdisciplinary research approaches providing the chance to jointly advance with related fields such as electrocatalysis are identified. Particularly, we elucidate additives, sulfur hosts, current collectors and functional interlayers/hybrid separators containing metal oxides, hydroxides and sulfides as well as metal-organic frameworks, bare metal and further metal nitrides, metal carbides and MXenes. Throughout this review article, we emphasize the close relationship between the intrinsic properties of metal-based nanostructured materials, the (electro)chemical interaction with lithium (poly)sulfides and the subsequent effect on the battery performance. Concluding the review, prospects for the future development of practical Li-S batteries with metal-based nanomaterials are discussed.